Research firm reputation and investors' reaction to research reports - Lei, Thi Quynh Giang (Nanyang Technological University, 2008)
The objective of this research is to study investors’ reaction to research reports issued on companies listed in the Singapore Stock Exchange (SGX). We examine the relationship between firm values and stock trading recommendations specified in analysts’ research reports. In addition, we investigate the abnormal returns in association with the research firms’ reputation as well as their ownership in the listed companies that they cover. Financial study analysis shows significant changes in the firm market value (or abnormal returns) on the day when the research reports are published. The statistical tests indicate that investors react strongly to analysts’ reports and follow recommendations of the research firms. We also find a statistically significant relationship between research firms’ reputation and the magnitude of investors’ reaction. Specifically, more reputable research firms generally produce larger changes in the market value (or abnormal returns) that are consistent with their recommendations. Contrary to our expectation, we do not find any significant relationship between research firms’ ownership in the listed companies and abnormal returns. Overall, our study suggests that the SGX-MAS Research Incentive Scheme facilitates investment decisions by providing new information that is of value to investors.